2019
DOI: 10.1136/bmjqs-2019-009456
|View full text |Cite
|
Sign up to set email alerts
|

The value of Facebook in nation-wide hospital quality assessment: a national mixed-methods study in Norway

Abstract: ObjectivesThe objective was to assess the possibility of using a combination of official and unofficial Facebook ratings and comments as a basis for nation-wide hospital quality assessments in Norway.MethodsAll hospitals from a national cross-sectional patient experience survey in 2015 were matched with corresponding Facebook ratings. Facebook ratings were correlated with both case-mix adjusted and unadjusted patient-reported experience scores, with separate analysis for hospitals with official site ratings an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…When we discovered an official hospital Facebook page, we validated the information by using the hospital’s website’s address, contacting hospital administrators, or referring to our operating definition of an official hospital Facebook page. These search methods have also been applied in previous studies [ 12 , 13 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When we discovered an official hospital Facebook page, we validated the information by using the hospital’s website’s address, contacting hospital administrators, or referring to our operating definition of an official hospital Facebook page. These search methods have also been applied in previous studies [ 12 , 13 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Facebook includes a review tool that enables users to write narrative evaluations and rate the performance of businesses and institutions on those organizations’ Facebook pages. Numerous studies have discovered a low to moderate connection between Facebook evaluations and metrics from systematic patient satisfaction surveys [ 12 , 13 , 24 ], while another study found that clinical quality indicators such as reduced readmission rates are linked with patient recommendations and higher Facebook ratings [ 25 ]. According to a recent study, hospitals with an active Facebook page had more “likes”, a higher rate of patients willing to recommend the hospital, and a better overall satisfaction score [ 26 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The only research area where the behavior of the population or users in social media platforms in relation to hospitals has been specifically addressed so far is the analysis of reviews of hospitals in social media platforms (e.g., on Yelp, Google Reviews, or Facebook). These studies have mostly examined the extent to which such reviews from the public correlate with official hospital quality statistics (Bjertnaes et al 2020;Campbell and Li 2018;Glover et al 2015;Lee et al 2018;Perez and Freedman 2018). In this regard, however, it was also noted that biases occur on social media platforms because parts of the population are not active on them or do not review hospitals on them (Bjertnaes et al 2020;Campbell and Li 2018;Rozenblum et al 2017;Huppertz and Otto 2018).…”
Section: Social Media and Hospitalsmentioning
confidence: 99%
“…These studies have mostly examined the extent to which such reviews from the public correlate with official hospital quality statistics (Bjertnaes et al 2020;Campbell and Li 2018;Glover et al 2015;Lee et al 2018;Perez and Freedman 2018). In this regard, however, it was also noted that biases occur on social media platforms because parts of the population are not active on them or do not review hospitals on them (Bjertnaes et al 2020;Campbell and Li 2018;Rozenblum et al 2017;Huppertz and Otto 2018). Furthermore, there are hardly any empirical findings to date on attitudes, preferences or user behavior of the population with regard to social media pages of hospitals.…”
Section: Social Media and Hospitalsmentioning
confidence: 99%